Prevalence of non-alcoholic fatty liver disease in postmenopausal woman: systematic review and meta-analysis - Xiong Xiao; Yang Liu; Yan Wei; Li He (IMR Press, 2021)
Background: Non-alcoholic fatty liver disease (NAFLD) has long been considered to be most prevalent chronic hepatic disease. However, the overall prevalence of NAFLD in postmenopausal women was largely unknown. Objectives: In the current study, we aimed to investigate the overall prevalence of NAFLD in postmenopausal women in order to provide more information for clinical work. Methods: A systematic search was conducted in Medline, Embase, web of science and Cochrane for articles in the English language from inception until May 2020. Wilson score method was used to calculate the 95% confidence interval (95% CI) and DerSimonian-Laird random-effects model with Freeman-Tukey double arcsine transformation was used for estimating pooled overall prevalence. Results: Our search returned 4465 records. After removed duplicates and screened titles, abstract and full content of articles, 25 studies were retrieved. Overall, the NAFLD prevalence was 30.81% (95% CI 24.75-37.22). The prevalence of NAFLD in postmenopausal women was 31.64% (95% CI 25.82-37.77) in Asia countries compared to 27.99% (95% CI 11.21-48.72) in Non-Asia countries. Ultrasound was the most commonly used diagnostic technique in diagnosing NAFLD in postmenopausal women, lead a higher prevalence of NAFLD (32.77%, 95% CI 27.43-38.35) than computed tomography (CT, 5.64%, 95% CI 4.82-6.52) or fatty live index (FLI, 17.33%, 95% CI 11.72-23.78, P < 0.01). Conclusion: Approximately one third of postmenopausal women presented with NAFLD indicated a rather high prevalence which call for the attention of primary care physicians, specialists, and health policy makers.